Trump tariffs and the U.S. defense industry - Jeroen Klomp (PLoS ONE, 2025)
In March 2018, U.S. President Trump announced that the U.S. would start imposing tariffs on steel and aluminum imports from most exporting countries around the world. This study explores the impact of introducing these tariffs on the equity return of U.S. defense companies. As the defense industry stands among the largest metal consumers in the U.S., it is expected that these import restrictions have deteriorated the business performance of the U.S. defense industry. For this study, a novel trade uncertainty indicator has been constructed that is based on the key events related to the invocation of Section 232 of the Trade Expansion Act. This section empowers the President to impose trade restrictions when the quantity of imports threatens to impair national security. My empirical analysis reveals that investors perceived the introduction of the steel and aluminum tariffs as detrimental to U.S. defense companies. The negative abnormal stock returns in the days around several key tariff-related events evidence this. Already in the period before the Department of Commerce released the findings of its investigation, investors were speculating on the possible introduction of trade barriers. However, the height of the imposed tariff exceeded their expectations since the negative sentiment was further reinforced after the official announcement of the tariff by President Trump.